1997
DOI: 10.1111/j.1467-8500.1997.tb01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on AJPA and Other Public Administration Journals

Abstract: I welcome the invitation of the current AJPA Editors, Glyn Davis and John Wanna, to write these reflections to accompany the decennial index and Catherine Althaus's article surveying what we have been talking about in AJPA over the past decade. In this endnote I want to say something about the mission of public administration journals (including AJPA), to offer a few comments about the editorial function, and also to refer to some exercises in comparing public administration journals. It may be appropriate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…When only looking at articles, 323 out of 1,059 authors (30.5 percent) were women; this is comparable to the finding of Kellough and Pitts (2005, 4) that 27.7 percent of articles between 2000 and 2003 were written by women. This also compares well to AJPA, with 730 males and 200 (21.5 percent) females between 1989 and 1995 (Wettenhall 1997, 191). It is possible that in Australia, too, the number of female authors publishing in AJPA has since increased.…”
Section: Quantitative Observations On Par 2000–2009supporting
confidence: 70%
See 3 more Smart Citations
“…When only looking at articles, 323 out of 1,059 authors (30.5 percent) were women; this is comparable to the finding of Kellough and Pitts (2005, 4) that 27.7 percent of articles between 2000 and 2003 were written by women. This also compares well to AJPA, with 730 males and 200 (21.5 percent) females between 1989 and 1995 (Wettenhall 1997, 191). It is possible that in Australia, too, the number of female authors publishing in AJPA has since increased.…”
Section: Quantitative Observations On Par 2000–2009supporting
confidence: 70%
“…Ross Curnow (1984, 315) observed that in the early 1980s, about 25 percent of articles in the Australian journal were written by practitioner authors. However, 10 years later, and against a trend visible elsewhere, Wettenhall (1997, 191) noted that 39 percent of AJPA articles in the 1989–95 period were written by practitioners. Looking at authorship in the Dutch journal Bestuurswetenschappen between 1947 and 1996, Raadschelders pointed out that practitioner authorship declined from more than 21 percent between 1947 and 1951 to less than 12 percent between 1992 and 1996 (1998, 29).…”
Section: Quantitative Observations On Par 2000–2009mentioning
confidence: 97%
See 2 more Smart Citations
“…Engagement with public servants remains a key challenge. Having said this, Wettenhall (: 190) makes the point that the academic–practitioner distinction is somewhat arbitrary, that many ‘pracademics’ publish in the field and that the fact that we exist as a professional discipline is a more‐telling feature; we should tailor to interaction between the interests of all engaged in the work of the public sector. I agree with this position and am persuaded by Wettenhall's plea to pursue AJPA as a repository of the public nature of the public sector task.…”
Section: Who Does the Talking? Assessing Our Contributors Over Timementioning
confidence: 99%